Vocational education in the Philippines in Spanish times - Liesch, James R. 1928- ([Quezon City University of the Philippines], 1952)
This is an investigation of the course offerings of the various Spanish vocational schools in the Philippines. The point of view of this investigation is to carry a modern frame of reference to the past.
Bibliography: p. 115-123.
Thesis (M.Ed.)--University of the Philippines, 1952
Typewritten
Vita
Keywords: Vocational education -- Philippines